Optimasi Desain Bottom Screen dan Sterilizer Pabrik Kelapa Sawit PT. XYZ - Hery Sumardiyanto; Rahmat Rahmat; Sulaiman Sulaiman (Journal of Innovative and Creativity, 2025)
The bottom screen is the part responsible for removing ripe fresh fruit bunches (FFB) from the sterilizer. This role is crucial in ensuring the smooth flow of ripe fruit out of the sterilizer without any obstacles. If the bottom screen is disturbed, the flow of fruit out will be hindered, which ultimately reduces the sterilizer's capacity. A deformed or blocked bottom screen can inhibit the release of ripe FFB. Therefore, a deeper identification of the problem is needed to design the right solution to increase the capacity and effectiveness of the sterilizer. If the bottom screen is disturbed, the flow of fruit out will be hindered, which ultimately reduces the sterilizer's capacity. Therefore, regular repair and maintenance of the bottom screen are crucial to ensure that the sterilizer process runs smoothly and production capacity remains optimal. it can be concluded that the two main problems that have the greatest impact are the blockage of FFB out due to deformation of the bottom screen (41%) and thinning of the sterilizer wall (24%), which cumulatively. fixing these two problems is a top priority in efforts to increase sterilizer capacity.